A step towards digital transformation within a utility company through process automation for a sustainable energy transition - Nhora Parra; Sandra Giraldo; David laRotta; Betsy Gómez; Yissel Mejía; Laidi Morales; César Nieto‐Londoño; Rafael E. Vásquez (The Journal of Engineering)
Abstract Sustainable energy management systems are part of the global energy transition by digitally transforming utility companies throughout the past decade. Industry 4.0 (4IR) has been adopted to improve competitiveness and align its processes with trends that require changes in the producer‐consumer relationship. This study examines how AES Colombia uses Industry 4.0 to improve efficiency and promote a sustainable energy transition. It focuses on automating key processes within the company's hydropower operations, representing 6% of Colombia's energy market. The research shows that robotic‐process‐automation technologies reduce pricing simulation time from 27 to 5 h and tax declaration manual labour from 1560 to 584 h. These advancements enhance operational efficiency and significantly improve decision‐making capabilities, thereby boosting the reliability of information utilized across various operational domains, including financial, market, and regulatory processes. The findings underscore the critical role of flexibility, cultural change, and continuous training in facilitating successful digital transformation initiatives. This work contributes to understanding how intelligent systems can optimize energy companies’ processes while promoting a human‐centred approach to Industry 4.0 technologies. The results underscore the importance of aligning technological advancements with sustainability goals to drive significant improvements in the energy sector, paving the way for a more resilient and adaptable energy landscape.